Safety and Efficacy of Loading Doses of Vitamin D: Recommendations for Effective Repletion - Béla E. Tóth; István Takács; Kristóf Kádár; Sara Mirani; Miklós Vecsernyés; Péter Lakatos (Pharmaceuticals)
Background/Objectives: Epidemiological data on vitamin D status revealed that, despite various dosage and durations of supplementation, the effectiveness often fails to achieve optimal outcomes. The need for higher doses than previously recommended was suggested, but several modifying factors should be considered, including the level of deficiency, and BMI. The objectives of this post hoc evaluation are to characterize treatment effectiveness based on the applied dose, duration and BMI; and to assess the safety aspects associated with rapid repletion of vitamin D. Methods: Vitamin D deficient subjects selected in the post-hoc analysis: seventy patients included from a combined loading-maintenance supplementation (300,000 IU followed by 60,000 IU) protocol and 62 deficient subjects who received a low-dose maintenance (1000 IU/day) therapy. The risk of overload and the incidence of hypercalciuria and hypercalcemia resulting from loading or post-loading maintenance were investigated. Results: The moderate–fast-loading schedule of 60,000 IU per week for 5 weeks, effectively achieves the target in 25(OH)D levels over 30 ng/mL for all deficient subjects, regardless of their BMI. Slower loading with lower weekly doses confirms the safety of supplementation, but the effectiveness is dependent on the subjects’ BMI; overweight and obese patients require higher doses to reach the same vitamin D levels. No difference in safety parameters observed compared to low-dose therapies. Conclusions: The loading treatment involving a total dose of 300,000 IU administered over 5 or 10 weeks is effective for repletion, does not lead to 25(OH)D overload, and poses no additional risks of hypercalcemia or hypercalciuria. Furthermore, there are no safety concerns regarding changes in bone resorption markers. A combination of the loading treatment with a subsequent maintenance dose of 2000 IU daily is adequate to achieve the target vitamin D levels.